SN 2021foa, a transitional event between a Type IIn (SN 2009ip-like) and a Type Ibn supernova - Reguitti A; Pastorello A; Pignata G; Fraser M; Stritzinger MD; Brennan SJ; Cai YZ; Elias-Rosa N; Fugazza D; Gutierrez CP; Kankare E; Kotak R; et al. (EDP SCIENCES S A, 2022)
We present photometric and spectroscopic data of the unusual interacting supernova (SN) 2021foa. It rose to an absolute magnitude peak of M-r & x2004;=& x2004;-18 mag in 20 days. The initial light curve decline shows some luminosity fluctuations before a long-lasting flattening. A faint source (M-r & x2004;similar to & x2004;-14 mag) was detected in the weeks preceding the main event, showing a slowly rising luminosity trend. The r-band absolute light curve is very similar to those of SN 2009ip-like events, with a faint and shorter duration brightening ('Event A') followed by a much brighter peak ('Event B'). The early spectra of SN 2021foa show a blue continuum with narrow (similar to 400 km s(-1)) H emission lines that, two weeks later, reveal a complex profile, with a narrow P Cygni on top of an intermediate-width (similar to 2700 km s(-1)) component. At +12 days, metal lines in emission appear and He I lines become very strong, with He I lambda 5876 reaching half of the H alpha luminosity, much higher than in previous SN 2009ip-like objects. We propose that SN 2021foa is a transitional event between the H-rich SN 2009ip-like SNe and the He-rich Type Ibn SNe.